Ankylosis and pseudoankylosis of the temporomandibular joint in 10 dogs (1993–2015) - Strøm, Peter C.; Arzi, Boaz; Cissell, Derek D.; Verstraete, Frank J. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2016)
Objective: To describe the clinical features and results of treatment of true ankylosis and pseudoankylosis of the temporomandibular joint in dogs.Methods: This study was a retrospective case series. Ten client-owned dogs that were presented for inability to open the mouth or a severely decreased range of motion of the temporomandibular joint were included. Information on the surgical procedures performed and the perioperative complications were documented. Three-dimensional printing of the skull was performed in four dogs.Results: Two dogs were diagnosed with temporomandibular joint ankylosis and seven dogs with pseudoankylosis. One dog had evidence of combined temporomandibular joint ankylosis and pseudoankylosis. Of the seven dogs with pseudoankylosis, six had an osseous fusion involving the zygomatic arch and mandible. Surgical treatment was performed in nine dogs and a revision surgery was needed in one dog. Follow-up ranged from five months to eight years (mean: 48.6 months). Eight out of nine dogs that were treated surgically regained the ability to open their mouth, but six dogs never regained a fully normal temporomandibular joint range of motion.Clinical significance: Temporomandibular joint ankylosis and pseudoankylosis are uncommon in the dog. Surgical treatment for temporomandibular joint ankylosis or pseudoankylosis in dogs is a successful option and carries a prognosis dependent on patient-specific abnormalities. Computed tomography complemented with three- dimensional printing is valuable for understanding the extent of abnormalities and for preoperative planning.Supplementary material for this paper is available online at http://dx.doi.org/10.3415/VCOT-15-11-0189.
Keywords: Ankylosis; pseudoankylosis; temporomandibular joint; dog; surgery; three-dimensional printing; 3D printing